Injuries in youth soccer: A subject review (Pediatrics, 2000)
The current literature on injuries in youth soccer, known as football worldwide, has been reviewed to assess the frequency, type, and causes of injuries in this sport. The information in this review serves as a basis for encouraging safe participation in soccer for children and adolescents.